Household Waste Management with The Utilization of Incinerator Technology - Aribowo, Didik; Permata, Endi; Purbohastuti, Arum Wahyuni (EQUATOR SINAR AKADEMIA, 2026)
The problem of household waste in the Serang region, particularly in Priyayi Village, has reached alarming levels and has impacted river pollution. This community service project aims to implement sorting-based waste management and utilize environmentally friendly incinerator technology as a solution for handling residual waste. The methods used included socialization of waste sorting into four categories (organic, inorganic, hazardous and toxic, and residue) and a demonstration of the use of a household-scale incinerator unit with a smoke filtration system. The results of the activity showed that the integration of the Waste Bank and incinerator technology can reduce the volume of residual waste by up to 90% at the source level. Furthermore, the use of BSF maggots has successfully decomposed 77 tons of organic waste since 2019. In conclusion, the combination of sorting education and appropriate technological innovation is effective in creating a clean environment and reducing dependence on landfills.